Early Intervention Program Through Bibliotherapy Approach For Reducing Fear In Orientation And Mobility Of Children With Visual Impairment - Euis Heryati; Endang Rochyadi; Oom Sitti Homdijah; Ehan Ehan (Jurnal Pendidikan Kebutuhan Khusus, 2021)
Orientation and mobility skills are special skills that must be mastered by children with visual impairment, thus an orientation and mobility intervention program is important to develop. Fear or anxiety in children with visual impairment related to orientation and mobility can be caused by fear from within the children or from the environment. Personality, motivation, psychosocial factor, and family and community attitudes all contribute to one's reaction to mobility activities independently. This research aims to reduce the fear of children with visual impairment in performing orientation and mobility activities by implementing an intervention program through bibliotherapy technique. This research is a case study research with a qualitative approach. Bibliotherapy was carried out on two young children with visual impairment. The results of the program implementation show that children's fear or anxiety could be reduced in both cases in this research as seen by autonomous moves of the two children from the mother and caregiver and began to learn to trace the walls of the room.